Paciente de sexo masculino de 47 años de edad con gastritis crónica - Gavilanez Palma, Diego Daniel (2018)
My present case study is about a male patient, who works as a receptionist in a hotel, with a history of arterial hypertension and a year ago he was detected Gastritis also leads a sedentary life and inadequate eating habits, so he comes to consulting nutritional with the Nutritionist, so that I evaluated it, so I will proceed to make an ABCD, Anthropometric, Biochemistry, Clinical and Dietetic evaluation. After having carried out all the corresponding tests, a diagnosis of OBESITY GRADE I WITH MODERATE CARDIOVASCULAR RISK is reflected, for which reason nutritional treatment will be done to achieve the objective that is to lose 1 kg of weight per week until reaching its ideal weight, in a way of short-term weight loss, to avoid long-term complications that lead to obesity if not treated in time, can lead to a cerebrovascular event, diabetes mellitus type 2, dyslipidemia, heart attacks, atherosclerosis, etc. You will be prescribed a Gastric Soft Diet for Diabetic, appropriate to your needs and requirements; with allowed foods such as cooked fruits and vegetables so that the gastric mucosa heals and does not get irritated, and avoiding irritating foods, acids, raw vegetables as they form more hydrochloric acid causing upset stomach. In addition, the patient is recommended to perform physical activity 5 times a week of 30 minutes each, which together with the prescribed diet will be a success, and will be achieved with the objective that is to lose the excess weight that has.